Social media and orthodontics: Are our patients scrolling?. (June 2022) - Siddiqui, Nausheen; Chia, Matthew; Sharif, Mohammad Owaise
Objective: To assess patients' awareness of the availability of information related to orthodontics on social media, and to explore patients' willingness to engage with social media to aid with orthodontic treatment. Design: Prospective cross-sectional survey. Setting: This survey was conducted at Croydon University Hospital orthodontic department. Participants: A total of 125 orthodontic patients, both new and in treatment. There were no exclusion criteria. Methods: All participants completed a questionnaire designed to explore their awareness, access to and utilisation of social media as well as their willingness to engage with social media to support orthodontic treatment. There were no age restrictions or exclusion criteria. Results: Of the patients, 99% had access to social media. Of these patients, 64% were aware that social media platforms were available to help with orthodontic treatment, 30% had utilised social media related to orthodontics, with the most popular platforms being Instagram (n = 17) and Snapchat (n = 12). Of the patients, 73% stated that they would be willing to use social media in the future to support orthodontic treatment. Conclusion: Social media can be engaging, accessible and versatile, and has been shown to be effective at improving patients' knowledge regarding orthodontic treatment. As such, it may be used as a valuable tool for information provision to engage orthodontic patients. Awareness of the availability of orthodontics content on social media is increasing; however, only one-third of participants had previously used it to aid with orthodontic treatment. Given the availability of information on social media targeted at orthodontic patients there is a need to assess the quality of this information and if appropriate navigate patients towards high-quality, effective resources.